The Religious Value in Helvy Tiana Rosa and Benny Arnas’ Hayya - Yulianti, Yulianti; Supriyono, Supriyono; Sutiyono, Akhmad; Maximilian, Aksendro (IJLHE: International Journal of Language, Humanities, and Education, 2020)
The purpose of this research was to find out and to analyse the religious values which were available in a literary work (novel) entitled "Hayya" by Helvy Tiana Rosa and Benny Arnas. It comprised the religious values between human and God, the religious values between human and human, as well as the religious values between human and himself/herself which were available in that novel. The method used in this research was a qualitative descriptive method, which analysed sentence by sentence concerning the religious values. Then, the data that have been collected were identified, analysed, described and interpreted based on the objectives that have been considered. Descriptive qualitative research was used because the data were collected in the form of words, and it also gave priority to the deepest understanding toward the interaction found between the concepts which were studied empirically. The results showed that the religious values that were described in this novel were the forms of religious values between human and God which comprised piety and trust; the religious values between human with human which comprised respect, helpful, forgiving, colloquy and good manners; as well as the religious values between human and himself/herself which comprised patient, humble, honest/trustworthy, sincere and disciplined. Hopefully, this novel could be useful for the readers and could be the inspiration for the young generation in gaining their future without forgetting the religious values.